2014
DOI: 10.4102/sajip.v40i1.1135
|View full text |Cite
|
Sign up to set email alerts
|

A structural model of job resources, organisational and individual strengths use and work engagement

Abstract: Orientation: Organisations will not be able to maintain a competitive advantage by merely focusing on the development of their employees’ weaknesses. Employees should also be provided with sufficient job resources and opportunities to develop and use their strengths, as this could lead to work engagement.Research purpose: To test a structural model of job resources, perceived organisational support for strengths use, proactive behaviour towards strengths use and work engagement amongst South African employees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 55 publications
2
48
0
3
Order By: Relevance
“…These results are in line with the results from previous research. A recent study by Botha and Mostert (2014) found that employees who are allowed to use their strengths at work experience higher work engagement.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…These results are in line with the results from previous research. A recent study by Botha and Mostert (2014) found that employees who are allowed to use their strengths at work experience higher work engagement.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…Recently, studies have also started to focus on the effect of strengths use and deficit correction (SUDCO) on engagement (Botha & Mostert, 2014;Els, Mostert & Van Woerkom, 2015;Keenan & Mostert, 2013;Stander et al, 2014;Van Niekerk, Mostert & De Beer, 2016;Van Woerkom et al, 2016). These studies confirmed the predictive value of both SUDCO on engagement.…”
Section: Introductionmentioning
confidence: 84%
“…In studies conducted by Botha and Mostert (2014) and Stander and Mostert (2013), POS for strengths use was found to have a significant positive relationship with work engagement. This is consistent with Buckingham's (2007) conclusion that those activities completed from a strengths approach are energising and will be performed with excellence, which practically can be less time-consuming.…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations